1995
DOI: 10.1111/j.1651-2227.1995.tb13683.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of xanthine oxidase to the systemic circulation during resuscitation from severe hypoxemia in newborn pigs

Abstract: Xanthine oxidase may contribute to oxygen free radical formation during reoxygenation after hypoxia, but in humans the enzyme is present in substantial amounts only in the liver and intestine. We developed a sensitive assay for xanthine oxidase using 14C-xanthine as substrate and investigated whether xanthine oxidase was released into the systemic circulation when 19 newborn pigs were resuscitated after severe hypoxemia. In five piglets plasma xanthine oxidase concentrations increased from undetectable levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In vivo there are sources of free radicals other than the neurons, such as endothelium, neutrophils, and circulating xanthine oxidase (29). Thus, the finding that the radicals produced by these neurons do not substantially contribute to neuronal death after oxygen and glucose deprivation should not be extended to a conclusion that free radicals are of minor importance in vivo as there are several sources of free radicals other than neurons.…”
Section: Discussionmentioning
confidence: 89%
“…In vivo there are sources of free radicals other than the neurons, such as endothelium, neutrophils, and circulating xanthine oxidase (29). Thus, the finding that the radicals produced by these neurons do not substantially contribute to neuronal death after oxygen and glucose deprivation should not be extended to a conclusion that free radicals are of minor importance in vivo as there are several sources of free radicals other than neurons.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, it has been presumed that hepatic XOR will be released into systemic circulation upon certain noxious stimuli, such as hyperglycemic conditions, and this may aggravate vascular function impairment [ 29 ]. Rootwelt demonstrated that the release of XOR into the circulation from injured tissues after hypoxia and subsequent re-oxygenation [ 30 ]. XOR is shown to appear in the systemic circulation after ischemia reperfusion in humans [ 31 ].…”
Section: Discussionmentioning
confidence: 99%